Implementation of Project Based Learning in Teaching Speaking to Students of Vocational School - Muyassaroh, Muflikhatun Nisa; Prasetiyowati, Eni (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Scientific approach has several methods that lead the students to be active in learning English applicative skills such as speaking. One of methods that can be considered for enhancing students’ speaking skill is project-based learning (PjBL). Vocational School teachers might often apply PjBL to speaking activities in learning process. Regarding to this fact, the researcher conducted a descriptive study to explore Inservice teachers’ definitions of project-based learning (PjBL) and their accounts on the meaning of their PjBL implementations. A purposive sample of six teachers from grades ten until twelve and several students in public schools participated. Observation, interviews, and document collection are used for gathering the data. The result of this research shows that through PjBL, teachers could cover speaking activities that support students’ development in speaking through PjBL.